Maximizing genetic representation in seed collections from populations of self and cross-pollinated banana wild relatives - Kallow, Simon; Panis, Bartholomeus; Vu, Dang Toan; Vu, Tuong Dang; Paofa, Janet; Mertens, Arne; Swennen, Rony L.; Janssens, Steven B. (Springer, 2021)
Background: Conservation of plant genetic resources, including the wild relatives of crops, plays an important and well recognised role in addressing some of the key challenges faced by humanity and the planet including ending hunger and biodiversity loss. However, the genetic diversity and representativeness of ex situ collections, especially that contained in seed collections, is often unknown. This limits meaningful assessments against conservation targets, impairs targeting of future collecting and limits their use. We assessed genetic representation of seed collections compared to source populations for three wild relatives of bananas and plantains. Focal species and sampling regions were M. acuminata subsp. banksii (Papua New Guinea), M. balbisiana (Viet Nam) and M. maclayi s.l. (Bougainville, Papua New Guinea). We sequenced 445 samples using suites of 16–20 existing and newly developed taxon-specific polymorphic microsatellite markers. Samples of each species were from five populations in a region; 15 leaf samples from different individuals and 16 seed samples from one infructescence (‘bunch’) were analysed for each population.